Hubungan Stress Parenting dengan Regulasi Emosi Ayah pada Masa Pandemi Covid-19 - SALSA ALTASYA ANDINIE; Indri Utami Sumaryanti (Bandung Conference Series: Psychology Science, 2023)
Abstract. To reduce the impact of the COVID-19 pandemic, the PSBB was implemented, which included a temporary school closure policy. Since the implementation of the home study system, parents have become stressed in parenting, which is called Stress Parenting. This can lead to violence against children. And this child abuse can be caused by a lack of Emotion Regulation ability in dealing with parenting stress during the COVID-19 pandemic. The purpose of this study was to find out how closely the relationship between Stress Parenting and Father's Emotion Regulation was during the COVID-19 pandemic. This study has 112 respondents whose parents are male or fathers in the city of Bandung, West Java. This study uses the Parental Stress Scale (PSS) for Stress Parenting and the Emotion Regulation Questionnaire (ERQ) for Emotion Regulation. This research is a quantitative research with the Sperman Rank correlation method, with the value of the correlation coefficient obtained is 0.928 > 0.05. Where it can be concluded that there is no relationship between Stress Parenting and father's emotional regulation during the COVID-19 pandemic. Abstrak. Untuk mengurangi dampak pandemi COVID-19 diberlakukanlah PSBB yang didalamnya terdapat kebijakan penutupan sekolah sementara. Sejak diberlakukannya sistem belajar di rumah, membuat orang tua menjadi stres dalam mengasuh anak yang disebut Stress Parenting. Hal itu dapat menimbulkan kekerasan pada anak. Dan kekerasan pada anak tersebut dapat disebabkan oleh kurangnya kemampuan Regulasi Emosi dalam menangani stres pengasuhan selama pandemi COVID-19. Tujuan penelitian ini adalah untuk mengetahui seberapa erat hubungan antara Stress Parenting dengan Regulasi Emosi Ayah pada masa pandemi COVID-19. Penelitian ini memiliki 112 responden orang tua laki-laki atau Ayah di kota Bandung Jawa Barat. Penelitian ini menggunakan Alat ukur Parental Stress Scale (PSS) untuk Stress Parenting dan alat ukur Emotion Regulation Questionnaire (ERQ) untuk Regulasi Emosi. Penelitian ini merupakan penelitian kuantitatif dengan metode korelasi Rank Sperman, dengan nilai Koefisien Korelasi yang diperoleh sebesar 0,928 > 0,05. Dimana dapat disimpulkan Tidak terdapat hubungan antara Stress Parenting dengan regulasi emosi ayah pada masa pandemi COVID-19 ini.